Ultrastructural and molecular characterization of diversity among small araphid diatoms all lacking rimoportulae. I. Five new genera, eight new species. Issue 6 (28th October 2016) - Li, Chun L.; Ashworth, Matt P.; Witkowski, Andrzej; Lobban, Christopher S.; Zgłobicka, Izabela; Kurzydłowski, Krzysztof J.; Qin, Song
Abstract : Pennate diatoms are important contributors to primary production in freshwater and marine habitats. But the extent of their diversity, ecology, and evolution is still largely unknown. This is particularly evident among the clades of pennate diatoms without raphe slits, whose diversity is likely underestimated due to their small size and features that can be difficult to discern under light microscopy. In this study, we described five new araphid genera with eight new species based on morphological observations (light and electron microscopy) and molecular data (nuclear‐encoded small subunit ribosomal RNA and chloroplast‐encoded rbc L and psb C): Serratifera varisterna, Hendeyella rhombica, H. dimeregrammopsis, H. lineata, Psammotaenia lanceolata, Castoridens striata, C. hyalina, and Cratericulifera shandongensis . We also transferred Dimeregramma dubium to Hendeyella dubia . Phylogenetic analysis of the molecular data revealed that all the newly established taxa fell into a monophyletic group, with Fragilariforma virescens located at the base. The group was composed by two subclades: one comprising Castoridens, Cratericulifera, and Plagiostriata, and the larger including also the rest of the new genera plus some of the smallest known diatoms, such as Nanofrustulum, Opephora, Pseudostaurosira, Staurosirella, and Staurosira with a high level of support. This study enhances the general knowledge on the phylogeny and biodiversity of a group of small araphid diatoms that have been generally poorly described both by electron microscopy and DNA sequence data.